Economics of Southern Pines With and Without Payments for Environmental Amenities in the US South - Paudel, Karuna; Dwivedi, Puneet (Frontiers in Forests and Global Change, 2021)
During the early 1900s, nearly 37 million hectares of land in the Southern United States were under longleaf pine (Pinus palustris) relative to the current area of only 1.6 million hectares. Several initiatives were launched to encourage longleaf pine restoration across southern states. This study compares the economics of southern pines (longleaf, loblolly (Pinus taeda), and slash (Pinus elliottii) to facilitate the decision making of family forest landowners and design suitable financial incentives for increasing the area under longleaf pine in the region. We simulated six growth and yield scenarios for selected southern pines over three site indices in the Lower Coastal Plain of South Georgia. We estimated land expectation values (LEVs) of each scenario for the three cases, i.e., payment for forest products, payment for forest products and net carbon storage, and payment for forest products, net carbon storage, and net water yield. Our findings show that pine straw income significantly increases the LEV of longleaf pine. The financial risk of growing longleaf pine is lower than other southern pines. Existing financial support through various governmental incentives or additional monetary support for ecosystem services provided by longleaf pine ecosystems are needed to increase the area under longleaf pine in the Southern United States, in general, and in South Georgia, in particular. However, a need exists to reevaluate the conservation values provided by longleaf plantations considering expected shorter rotation ages due to the income provided by pine straw markets in the Southern United States.